Disease Outbreaks and Manmade Disaster in Ethiopia Short Communication - Tegegne, Kaleab Tesfaye; Geta, Medhin; Assefa, Abiyu Ayalew; Bagajjo, Wosenyeleh Semeon; Zeleke, Demelash; Tegegne, Eleni Tesfaye; Tessema, Mekibib Kassa (International Journal For Research In Health Sciences And Nursing, 2021)
Manmade disaster in Ethiopia occurred starting from November of 4/ 2020 as a result TPLF terrorist groups. The real cause of TPLF terrorist group’s conflict with Ethiopian government is the Manifesto 68 of TPLF.The most conspicuous feature of the Manifesto 68 is its reformulation of the people of Tigrai’s fight as a struggle to establish an ‘independent republic’. This objective of creating a separate Tigraian state was in marked contrast to the movement’s original aim. It is therefore necessary to ask why and how this new change took place. As mentioned earlier, and as the elasticity of ethnic nationalism dictates, not all members of the movement had been happy or fully convinced about the value of creating a united country on the basis of equality, as was envisaged in the original programme. Some members remained sceptical and were biding time to reverse this aim to replace it with their own ideas. In fact, the authors of the new direction set out in the Manifesto 68 were none other than the individuals within the leadership who had been waiting for an opportune moment to impose their wishes on the other members of the movement. Rewriting the original programme in detail (but not altering it) was a previous decision taken by the entire leadership, but which now became a pretext for derailing it.